2021
DOI: 10.3390/ijerph19010024
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Occupational Heat Stress and Noise Exposure with Carotid Atherosclerosis among Chinese Steelworkers: A Cross-Sectional Survey

Abstract: Occupational exposure to heat stress and noise at the workplace are widespread physical hazards and have been associated with an increase in both morbidity and mortality. This study aims to examine the association between occupational heat stress and noise exposure and carotid atherosclerosis in Chinese steelworkers. A total of 3471 subjects were included in this study. Carotid plaque was measured using ultrasonography. The occupational information was collected by face-to-face personal interviews and all of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The workload is an activity that requires the ability and expertise to do mandatory things in the form of physical and psychological within a particular time [25], and any work that requires muscle strength and the subject's thinking [26]. The workload is the amount of work that must be done, and completed by a person, either individually or in a team, between the amount of work volume and working time [27].…”
Section: Discussionmentioning
confidence: 99%
“…The workload is an activity that requires the ability and expertise to do mandatory things in the form of physical and psychological within a particular time [25], and any work that requires muscle strength and the subject's thinking [26]. The workload is the amount of work that must be done, and completed by a person, either individually or in a team, between the amount of work volume and working time [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other sociodemographic information was also collected using a questionnaire on age, sex, and educational level. Four occupational hazard factors (heat stress, noise, dust, and carbon monoxide) were measured by a qualified third-party company, in accordance with the National Occupational Health Standards of the People's Republic of China 17–19 …”
Section: Methodsmentioning
confidence: 99%
“…Four occupational hazard factors (heat stress, noise, dust, and carbon monoxide) were measured by a qualified third-party company, in accordance with the National Occupational Health Standards of the People's Republic of China. [17][18][19]…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Numerous studies have demonstrated that long-term heat exposure in the workplace can signi cantly increase the risk of cardiovascular diseases (9)(10)(11)(12), while the potential mechanisms remain unclear. Dyslipidemia plays a pivotal role in the onset and progression of cardiovascular disease (13).…”
Section: Introductionmentioning
confidence: 99%